A Review on Extraction of Antioxidants from Mangifera Indica L. (Mango) Peel and Seed with Highest Extraction Yield - Hazarudin, Nur Hanis (Progress in Engineering Application and Technology, 2021)
Mangoes are rich with flavonoids and carotenoids with abundance of bioactive compounds that are suitable to be extracted and apply into various type of food as food additives. Mangoes are usually consumed in fresh or processed to extract it pulps and juices which causes bio-waste production. The peels and seeds are rarely used in food production, though it contained a considerable concentration of bioactive compounds which can be a functional component in preserving food. Presence of preservatives in food can inhibit the oxidation process within the food, preserving the taste, color and nutritive value. The extraction of natural antioxidants are being focused to obtain low-cost antioxidants to replace synthetic antioxidants. Moreover, recent researchers have been developing more efficient techniques of extraction for obtaining greater value of antioxidant extracts from various type of plants such as, Ultrasound-Assisted Extraction (UAE). There are several stages to extract bioactive compounds such as, the solvent is needed to penetrate into the solid matrix then solute must be dissolved in the solvent in order to diffuse out the solute from the solid matrix to collect the extracted solutes. The solubility of extraction performance can be affected by the properties of extraction solvent, the particle size of the raw materials, the solvent-to-solid ration, the extraction temperature and the extraction duration. This study will be conducted to review using Preffered Reporting Items for Systematic Review and Meta-Analyses (PRISMA) on suitable extraction method with highest extraction yield, characterization of antioxidant properties between peel and seed of fruits and evaluation of natural antioxidants applied on food. This study could contribute in future studies for highest extraction yield of bioactive compounds.